Debt and Deficit Growth Rate Reporting for Post-Communist European Union Member States - Andrzej Paczoski (Social Sciences, 2019)
A focalized analysis and reporting on the problems of general government debt (GGD) and government deficit (GD) and their influencing factors on economic growth rate tell the story of positive, neutral, and negative economies. Research was conducted over a nineteen-year period between 2000 and 2018 on all eleven post-communist European Union Member States (MS). MSs are divided in to three regional blocks: (1) the Baltic countries, (2) Central and Eastern European countries, and (3) the Balkan countries. Reviewed literature examined different types of GGD and GD with denoted influence on each MS’s economy and government. GGD and GD increase as a result of State intervention by reacting to economic fluctuations needed in creating redistributive-related fiscal policy. A breakdown of the problems of fiscal policy is explained. Datasets were compiled and systematically analyzed using Eurostat indicators. European regulatory benchmarking was used for GGD and GD as a percentage of gross domestic product. Results were divided at the regional group level. Comparative tax systems based on total general government revenue as well as total tax and contribution rate were evaluated. Histo-geographical research was considered and a comparative examination of GGD, GD and growth rate illustrated. In terms of GGD, GD, and growth rate, the Baltic countries were best situated, while all other countries were generally stable—with the exception of Hungary, Croatia, and Slovenia. In all, negative or stagnant periods revealed a general positive trend throughout the study with the exception of the world financial crisis of 2008, in which a deteriorative impact on growth rate was evident in all MS—especially from 2009. In the latter years, MSs’ economic promise signals a high potential for renewed public finance and stability initiatives.